Rare adverse events associated with BNT162b2 mRNA Vaccine (Pfizer-BioNTech): a review of large-scale, controlled surveillance studies - Yong, Shin Jie *; Halim, Alice; Halim, Michael; Al Mutair, Abbas; Alhumaid, Saad; Al-Sihati, Jehad; Albayat, Hawra; Alsaeed, Mohammed; Garout, Mohammed; Al Azmi, Reyouf; Aldakheel, Noor; Alshukairi, Abeer N; et al. (MDPI, 2022)
Given the increasing anti-vaccine movements erroneously touting vaccine danger, this review has investigated the rare adverse events potentially associated with BNT162b2 (Pfizer-BioNTech), an mRNA vaccine against the severe acute respiratory distress syndrome coronavirus 2 (SARS-CoV-2). Only real-world surveillance studies with at least 0.1 million BNT162b2-vaccinated participants and one unvaccinated control group were selected for review. A total of 21 studies examining the potential association of BNT162b2 with cardiovascular, herpetic, thrombotic or thrombocytopenic, neurological, mortality, and other miscellaneous rare adverse events were described in this review. Only myocarditis is consistently associated with BNT162b2. An unclear direction of association was seen with stroke (hemorrhagic and ischemic), herpes zoster, and paresthesia from BNT162b2, which may require more studies to resolve. Fortunately, most surveillance studies detected no increased risks of the remaining rare adverse events reviewed herein, further reassuring the safety of BNT162b2. In conclusion, this review has concisely summarized the current rare adverse events related and unrelated to BNT162b2, arguably for the first time in sufficient depth, to better communicate vaccine safety to the public.